Integrating issues of biodiversity and climate change to achieve sustainable forest management: A case of Mbeliling landscape, Flores. Issue 1 (November 2021) - Adinugroho, W C; Krisnawati, H; Imanuddin, R; Ayat, A; Wirastami, L A; Kusmana, C
Abstract: Biodiversity and climate change are interrelated, so a coordinated approach is needed to cover it by focusing on how landscapes provide many benefits. The Mbeliling landscape, Flores is the smallest management unit in an ecological perspective, essential for the conservation and preservation of biodiversity, especially for the endemic birds of Flores. Efforts to preserve biodiversity are also expected to contribute to climate change mitigation and adaptation. The study aims to produce data and information on biodiversity and potential carbon stocks at the land cover of the Mbeliling landscape. Desk study and field survey were used to answer research questions. The Mbeliling landscape has eight types of tree vegetation land cover that can serve as carbon sinks and the habitat for four species of Flores endemic birds. Approximately 139 species of vegetation with the total carbon stocks could potentially absorb the carbon dioxide in the atmosphere of ± 103.63 Mt CO2 -e. The type of land cover significantly influences carbon stocks. The land cover with forest category in the Mbeliling landscape has the most extensive carbon stock among other land cover types. This result can be used as a reference in managing the Mbeliling landscape in integrating efforts to conserve biodiversity and mitigate climate change through the REDD+ scheme.